Phenotypic and integrated analysis of a comprehensive Pseudomonas aeruginosa PAO1 library of mutants lacking cyclic-di-GMP-related genes - Eilers, Kira; Kuok Hoong Yam, Joey; Morton, Richard; Mei Hui Yong, Adeline; Brizuela, Jaime; Hadjicharalambous, Corina; Liu, Xianghui; Givskov, Michael; Rice, Scott A.; Filloux, Alain (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is a Gram-negative bacterium that is able to survive and adapt in a multitude of niches as well as thrive within many different hosts. This versatility lies within its large genome of ca. 6 Mbp and a tight control in the expression of thousands of genes. Among the regulatory mechanisms widely spread in bacteria, cyclic-di-GMP signaling is one which influences all levels of control. c-di-GMP is made by diguanylate cyclases and degraded by phosphodiesterases, while the intracellular level of this molecule drives phenotypic responses. Signaling involves the modification of enzymes’ or proteins’ function upon c-di-GMP binding, including modifying the activity of regulators which in turn will impact the transcriptome. In P. aeruginosa, there are ca. 40 genes encoding putative DGCs or PDEs. The combined activity of those enzymes should reflect the overall c-di-GMP concentration, while specific phenotypic outputs could be correlated to a given set of dgc/pde. This notion of specificity has been addressed in several studies and different strains of P. aeruginosa. Here, we engineered a mutant library for the 41 individual dgc/pde genes in P. aeruginosa PAO1. In most cases, we observed a significant to slight variation in the global c-di-GMP pool of cells grown planktonically, while several mutants display a phenotypic impact on biofilm including initial attachment and maturation. If this observation of minor changes in c-di-GMP level correlating with significant phenotypic impact appears to be true, it further supports the idea of a local vs global c-di-GMP pool. In contrast, there was little to no effect on motility, which differs from previous studies. Our RNA-seq analysis indicated that all PAO1 dgc/pde genes were expressed in both planktonic and biofilm growth conditions and our work suggests that c-di-GMP networks need to be reconstructed for each strain separately and cannot be extrapolated from one to another.